Association between sleep duration and obesity is modified by dietary macronutrients intake in Korean. Issue 4 (July 2016) - Doo, Miae; Kim, Yangha
Summary: Background: Short sleep duration has been reported to be inversely associated with risk of obesity. Methods: The effects of sleep duration on obesity-related variables and the interaction of sleep duration and dietary macronutrients consumption on risk of obesity were analysed in 14, 111 subjects aged 20–79 from the Korean National Health and Nutrition Examination Survey. Results: Sleep restriction to less than 7 h per day resulted in higher body mass index, plasma triglyceride level, and obesity prevalence for women, but not for men. Protein intake was significantly lower in subjects with lower sleep duration for both men and women. The subjects with short sleep duration were significantly higher fat consumption for men, whereas carbohydrate consumption for women. Among subjects whose carbohydrate consumption was above the median, subjects with sleep duration of less than 7 h per day increased their odds of being obese (OR = 1.255, 95% CI: 1.073–1.476, P < 0.001) compared to subjects with sleep duration more than 7 h per day for women. Conclusions: Our results showed that sleep duration positively correlated with protein consumption, but negatively correlated with carbohydrate consumption, which might lead to high risk of obesity for women. Also, our findings support a significant association between sleep duration and obesity-related variables and this association has been potentially modified by dietary macronutrients consumption in women subjects.